Mental Resilience in the Story of Maryam in QS. 19: 23-26 - Susanto, Atikah Septiani; Nurrohim, Ahmad (Universitas Muhammadiyah Surakarta, 2024)
This research departs from the importance of the relationship between mental health and faith, which is believed to be achieved through patience, sincerity, gratitude, and tawakal to Allah. In Quraish Shihab's view, dhikr and righteous deeds also play a role in optimizing one's potential to achieve happiness in this world and the hereafter. This study aims to reveal how mental health in Islam is closely related to faith and the alignment of this concept with Dr. Susan Kobasa's theory of mental resilience. According to psychologist Susan Kobasa's research, there are three elements that seem to be important for a stress-resistant mindset to form: challenge, self-control, and commitment. Quraish Shihab asserts that true happiness does not only come from the fulfillment of physical needs, but especially from closeness to Allah and the attainment of the meaning of life. The research method used is qualitative research with a thematic interpretation approach. Primary data comes from Tafsir Al-Misbah, while secondary data is obtained from various literature such as books, journals, and other sources. This method aims to understand the concept of mental health in Islam more systematically and shows that from Maryam's story, we can gain mental resilience through faith and trust in Allah. The results of the study show that the teachings of the Qur'an, if understood and practiced properly, can be the main foundation in maintaining mental health.